Perancangan Sistem Informasi Pemasaran Aneka Rajut Menerapkan E-Commerce Pada Toko Bizhie Handmade Menggunakan Bahasa Pemrograman PHP Dan Database MySQL - melanie, Vanesaputri; Rianti, Eva (Riset Sinergi Indonesia, 2023)
Along with the development of communication and computer technology and the expansion of global trade, human needs for fast and accurate information are increasingly increasing. Bizhie Handmade is an MSME business (Micro, Small and Medium Enterprises) located in the city of Padang, which produces several kinds of knitwear using knitted basic materials. The products are produced by themselves, starting from designing the product, creating the product and then selling the product to consumers. So far, the sales process for Bizhie Handmade is still carried out on an ongoing basis. manual such as sales and marketing of products in conventional stores. Through a website-based marketing system, you can have a great opportunity to develop your business by offering your products online to buyers without having to meet face to face and with a wider scope that can offer products on websites on the internet. The aim of this research is to build a marketing website for various knitwear which provides information about the products being marketed to make it easier for customers to order various knitwear on Bizhie Handmade, which is implemented in the PHP programming language and MySQL as the database. The data processed in this research is sales transaction data in the form of reports originating from Bizhie Handmade. With this website, it is hoped that it can help all activities at Bizhie Handmade.